A Radiologic Review of Tuberculosis (International Journal of Food and Nutritional Sciences, 2022)
Tuberculosis has made a comeback in nonendemic communities, a development ascribed to causes such as increasing migration as well as the human immunodeficiency pandemic. Although the thorax is the most commonly affected organ system, tuberculosis can affect any of the organ systems (e.g., the respiratory, central nervous, musculoskeletal, cardiac, gastrointestinal, but also genitourinary systems), and timely diagnosis is critical because delayed treatment is linked to severe morbidity. Unfortunately, a history of TB infection or exposure may or may not be present, while active tuberculosis is only found in around half of the cases. A tuberculin skin test that is negative does not rule out infection. Furthermore, TB' clinical and radiologic characteristics may be mistaken for those of a variety of other illnesses. Although biopsy and culture specimens are often needed to establish a definite diagnosis, it is critical for radiologists and physicians to grasp the usual TB distribution, patterns, and imaging symptoms.